A Resident-Led Quality Improvement Initiative to Improve Obesity Screening - Laiteerapong, Neda (2011)
Instruction on quality improvement (QI) methods is required as part of residency education; however, there is limited evidence regarding whether internal medicine residents can improve patient care using these methods. Because obesity screening is not done routinely in clinical practice, residents aimed to improve screening using QI techniques. Residents streamlined body mass index (BMI) documentation, created educational materials about obesity, and launched an obesity screening QI initiative in a residency clinic. Residents designed plan-do-study-act cycles focused on increasing awareness and maintaining improvements in screening over a 1-year period. Documentation rates were collected at baseline, 2 weeks, 6 months, and 1 year post-intervention. At 1 year, obesity treatment rates also were collected. BMI documentation rates after 1 year were higher than baseline (43% vs 4%, P < .0001). In obese patients, BMI documentation was associated with lifestyle counseling (34% vs 14%, P < .01). An internal medicine resident-led QI project targeting obesity can improve screening.